Genetic Diversity and Kinship Relationships Among Black Mangrove Populations (Rhizophora mucronata) in West Sulawesi Based on Morphological Markers - Mukrimin, Mukrimin; Gusmiaty; Salam, Marwah; Muslimin, Atisa (Foresty Faculty of Hasanuddin University, 2025)
Rhizophora mucronata is a black mangrove with the most productive ecosystem that has benefits many people. But in reality, because of their business, some people often neglect preserving mangrove ecosystems and habitats. This study was conducted to analyze the level of genetic diversity and the relationship between R. mucronata in West Sulawesi based on morphological markers that will be used in future restoration efforts of black mangroves around the coast. This study used ten trees from three origins: Polewali Regency Mandar, Majene, and Mamuju. Then, several parts of the tree are used for this study, namely leaves, trunks, bark, roots, flowers, and propagules. However, the observed characteristics are leaf shape, stem shape, and color samples such as bark color, stem color, root color, color propagule (fruit and hypocotyl), and leaf color with a qualitative and quantitative approach. The results of this study show that black mangroves in Polewali Mandar, Majene, and Mamuju show high-value genetic diversity. The genetic distance between Polewali Mandar and Mamuju shows a high value of 0.13, meaning they have a distant kinship. Meanwhile, the genetic distance between Polewali Mandar and Majene shows a low value of 0.09, meaning they are close relatives. The findings of this study directly address the research urgency by highlighting the high genetic diversity of R. mucronata populations in West Sulawesi, despite increasing threats from anthropogenic activities. The observed genetic distances indicate significant variation among populations, particularly between Polewali Mandar and Mamuju, which suggests the need for targeted conservation strategies. The close genetic relationship between Polewali Mandar and Majene further emphasizes the importance of localized preservation efforts. These insights provide a scientific basis for future restoration initiatives, ensuring conservation programs maintain genetic resilience and adaptability within the mangrove ecosystem.